MENA and Public Consultations - Bteddini, Lida (World Bank, Washington, DC, 2013)
The integration of consultation mechanisms throughout the policymaking process has proved to be a valuable instrument to help strengthen government-citizen interaction and improve the quality of government policies on key development areas by leading to better designed development projects, more effective service delivery, and improvements in the targeting of benefits. By making preliminary policy analysis available for public scrutiny, stakeholders are provided with a means to inform the development of a policy or its implementation. Consultation also helps regulators to balance opposing interests and to identify unintended effects while ensuring transparency to minimize administrative burdens and reduce corruption and rent-seeking. When successful, public participation can have a transformative impact by providing citizens with a platform for active engagement in the development process, and allows citizens to hold governments to account and to better influence decisions that affect their lives. While the benefits of public consultation are widely recognized, the MENA region still lags in the domain of public engagement, especially in regards to providing citizens with mechanisms to engage effectively in the design, implementation, and evaluation of public policy.